Inside Cover: Novel 1, 4‐Substituted‐1, 2, 3‐Triazoles as Antitubercular Agents (ChemMedChem 5/2015). Issue 5 (May 2015) - Altimari, Jarrad M.; Hockey, Samantha C.; Boshoff, Helena I.; Sajid, Andaleeb; Henderson, Luke C.
<x xml:space="preserve">Abstract</x> The inside cover picture shows that 30 % of the world population is infected with TB. In 2013, it caused 1.5 million deaths, and the incidence of drug resistance is increasing. TB's prevalence in low‐ and medium‐income countries means that new therapies must be accessed quickly and cheaply. Simple 1, 2, 3‐triazoles were assembled via click chemistry in high crude purity and in moderate to high yield, and serve as excellent starting points for development of potent therapies. For further details, see the Communication by Luke C. Henderson et al. on p. 787 ff.